The Influence Of Accounting Information Systems, Internal Control Systems And The Implementation Of Good Corporate Governance In Efforts To Prevent FRAUD - Muhammad Irfan Florid; Rudi Feri Hendra; Pupung Purnamasari (Return : Study of Management, Economic and Bussines, 2023)
Fraud, corruption, misuse of assets, and embezzlement of funds are still a scourge for most companies, especially companies engaged in financial services. This is because the processing of work that has been divided into tasks and authorities and the expansion of supervision of company elements makes the scope of supervision wider. The writing method used in this scientific article is a qualitative method and literature review (Library Research). In studying theories and relationships, ausality or influence between variables comes from books and journals that are accessed offline or online. from Google Scholar, Mendeley, or other online media. This scientific article is a qualitative descriptive type that emphasizes the actual problem and research that describes the Effects of Accounting Information Systems, Internal Control Systems, and the Implementation of Good Corporate Governance in Efforts to Prevent Fraud. This study aims to determine how accounting information systems, systems influence Internal Control and Implementation of Good Corporate Governance in Efforts to Prevent Fraud with the method used is to conduct a literature review of relevant previous research. These results indicate that the Accounting Information System,iInternaliControliSystemianditheiImplementation of Good Corporate Governance I have an affection Fraud Prevention. The conclusions from the results of the literature test in this study are as follows: The Accounting Information System has a positive effect on Fraud Prevention, and Internal Control has a positive effect on Fraud Prevention. The implementation of Good Corporate Governance has a positive effect on Fraud Prevention.